Identification of Automatic Stabilizers Among the Instruments of the Monetary Policy of Romania Regarding the Maastricht Inflation Criterion: Array - Ailincă, Alina Georgeta (Acta Universitatis Danubius. Œconomica, 2020)
The global financial and economic crisis has left deep wounds on the world's economies, whose scars are still being seen today, and the need for economic, financial, political and social stabilization seems increasingly acute. In this context, the ability to smooth the volatility of economic output of automatic stabilizers stands out. If we discuss strictly convergence, the Maastricht criteria can also be included in an automatic stabilization paradigm. In this context, based on previous work, the article aims to develop a way to identify automatic stabilizers for inflation in Romania, starting from the classical instruments of the monetary policy of the National Bank of Romania.